ANALISIS EKONOMI ISLAM TERHADAP PRAKTIK E-COMMERCE DALAM PERSPEKTIF FIQIH MUAMALAH - Syawal Tawakkal Asdar; Dimas Adi Saputra; Ahmad Baehaki; Muhammad Ridho Azka (Taksasila Edukasi Insani, 2025)
This research examines the suitability of e-commerce practices with the principles of fiqh muamalah in Islam, especially in the aspects of transaction validity, justice, consumer protection, and the application of business ethics. The method used is descriptive qualitative with a literature research approach to analyze Islamic economic theory, fiqh muamalah regulations, and their relevance to digital transaction practices. The research data was obtained from secondary literature sources, including books, scientific journals, fatwas from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), as well as references from the Qur'an and Hadith.The results show that e-commerce practices are acceptable in Islam as long as they fulfill principles such as transparency, honesty, and transaction security. Salam and istisna' contracts are identified as the most suitable contracts for digital transactions as they fulfill the terms and conditions stipulated in Islamic law for buying and selling. However, challenges such as uncertainty (gharar), usury, fraud (tadlis), and gambling (maisir) need attention through regulation and the application of business ethics based on Islamic law. This research is expected to contribute to business people, policy makers, and academics in integrating Islamic economic values with technological advances to build a fair and sustainable business ecosystem.Keywords: E-commerce, Fiqh Muamalah, Islamic Economics, Salam Contract, Maqashid Sharia.